Martinus Martini: Ein wenig bekannter Geograph hoher Geltung - Schmidt-Pretoria, Werner (ERDKUNDE, 1956)
Martinus Martini, the central figure of this essay, has scarcely been mentioned in current publications on the geography of the Far East, despite the fact that this member of the Order of Jesus ought to be regarded as one of the greatest scientists of the 17th century. Not only did he cover on foot thousands of miles within the old Chinese Empire, he also made known facts and put forward theses most of which still hold good today. This essay presents for the first time in print a short biographic sketch of this noble scientist and at the same time gives a considerable amount of information about the general conditions existing in China between the years 1650 and 1660. Another interesting point is that within this period some of his companions came to be leading mathematicians and astronomers at the Peking Imperial Court and that a few of them even tried and succeeded in travelling from there to Europe by a land route.